Penerapan Model Pembelajaran Kontekstual Untuk Meningkatkan Hasil Belajar Siswa Agama Buddha Kelas VII SMP Negeri 1 Mandiraja - Yogi Kristiawan; Novianti Novianti; Dwi Maryani Rispatiningsih (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to determine the results of the application of contextual learning in improving the learning outcomes of seventh grade Buddhist students of SMP Negeri 1 Mandiraja. The formulation of the problem in this study is how to improve learning outcomes after applying the contextual learning model to Buddhist students of class VII SMP Negeri 1 Mandiraja. This research is an experimental type of research with the type of One Shoot Case Study. The research was conducted by means of observation, action (treatment), and results. The subjects of this study were Buddhist students in class VII, which consisted of 2 students and 1 student. Data collection techniques through observation, interviews, documentation, and tests. The data analysis technique used qualitative techniques (in the form of observation notes, and documentation) and quantitative techniques. The results of this study indicate that the learning outcomes of Buddhist students have increased after the application of the contextual learning model, the results before the action of the overall learning outcomes of the three students averaged a score of 75, while after the overall action the students achieved an average score of 83.33. The conclusion of this research is the contextual learning model can improve the learning outcomes of seventh grade Buddhist students at SMP Negeri 1 Mandiraja, this is evidenced by the increase in learning outcomes after the action.